The liquid sacred in postmodern society - Mariański, Janusz (Przegla̜d religioznawczy, 2015)
The goal of this article is to show how cyberculture is described as a source of spiritual experiences. The fact that technical media and especially computers enabled new forms of sensation led to questioning their material status. Many of theoreticians said that cyberculture is by itself a basis for spiritual experiencing the world. In this article will be examined this claim referring to phenomena such as tribalization, decorporalization, information overload, to research if in cyberculture there could exists a new type of spiritual experience. General outcome of analysis is complex and needs further investigation because of necessity of inventing new ways of describing human way of experiencing spirituality in cyberculture.